1979
DOI: 10.1042/bj1840669
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hypophysectomy on liver nuclear ribonucleic acid synthesis in aging rats

Abstract: Changes in RNA synthesis in liver nuclei were observed at different ages and after hypophysectomy and hormone replacement in female Sprague-Dawley rats. As determined by the incorporation of [3H]UMP into an acid-insoluble product, RNA synthesis decreased by about 75% in intact rats from 6 months to 24 months of age. This decline with age was not observed in liver nuclei from 24-month-old rats that had been hypophysectomized at 12 months and maintained on a minimal hormone-replacement therapy. Thyroid hormones … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
12
1

Year Published

1986
1986
2007
2007

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 29 publications
3
12
1
Order By: Relevance
“…No changes in the level of RNase activity were observed between the adult and senes cent Wistar rat liver nuclei as also reported with nuclei isolated from other strains of rats [7,13] and from mice [9], However, the present results suggest that the RNA (or some fraction of it) synthesized by senescent nuclei may be somewhat more susceptible to RNase than is the RNA synthesized by adult nuclei. This intriguing possibility deserves further study.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…No changes in the level of RNase activity were observed between the adult and senes cent Wistar rat liver nuclei as also reported with nuclei isolated from other strains of rats [7,13] and from mice [9], However, the present results suggest that the RNA (or some fraction of it) synthesized by senescent nuclei may be somewhat more susceptible to RNase than is the RNA synthesized by adult nuclei. This intriguing possibility deserves further study.…”
Section: Discussioncontrasting
confidence: 51%
“…Several studies [7,9,13,16,28] have shown that RNA synthesis by liver nuclei isolated from various strains of senescent rats (24-30 months) or mice (25-30 months) is decreased compared, respec tively, to nuclei isolated from adult rats (12 months) or mice (8-10 months). The present results show that both the rate and the max imal level of RNA synthesis by liver nuclei isolated from senescent (22-26 months) fe male Wistar rats also are decreased com pared to adult (12 months) animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are no alterations in RNA polymerase activity along the lifespan (33), which indicates that low RNA synthesis in old animals would be a consequence of increased chromatin packing states, and not of reduced polymerase activity (31). Many studies involving chromatin resistance to digestion by restriction enzymes and nucleases showed a compactness increase in chromatin packing with aging (34)(35)(36).…”
mentioning
confidence: 99%
“…Thus, RNA polymerase I activity in isolated liver nuclei was reported to be stimulated after the administration of hormones such as glucocorticoids (Jacob et al, 1969 ;Yu and Feigelson, 1971;Sekeris and Schmidt, 1973;Todhunter et al, 1978;Grote et al, 1983;Matsui et al, 1986), thyroid hormones Zoncheddu et al, 1977;Igarashi et al, 1980), androgen and somatotropin Salaman et al, 1972;Bolla and Denckla, 1979). The underlying molecular mechanisms involved in the regulation, however, remain unclear.…”
mentioning
confidence: 99%